School Dropout of Adolescent Mothers in a Colombian-Venezuelan Border (2019)
The objective of this study was to compare school dropout of adolescent mothers in the Venezuelan-Colombian border, between the Táchira State and the North of Santander Department. The factors considered by the analysis were the age when leaving their studies, the educational level and the school performance before the desertion for determining the requirements conducive to social development. Thus, using a quantitative methodology, the study handles two samples: 235 adolescent mothers in Táchira State and 406 mothers in the North of Santander Department. The results indicate, for both contexts, a statistically significant association between school dropout before pregnancy with age at the time of dropout of school, with the educational level upon leaving school and the independence with previous academic performance. The study revealed that, in the abandonment of studies, the sociological age influences by an advance of roles not linked to chronological age. The conclusion is that a quality education that involves professional preparation and stops adolescent pregnancy through curricular planning according to childhood and youth that motivates intrinsically and extrinsically towards a better future is required in the studied reality.